Bioactive and Antioxidant Potential Agaricus bisporus Extracts Obtained by Different Extraction Methods and UV‐B Irradiation - Seung Woon You; Veronika Šimora; Eva Ivanišová; Ivona Jančo; Zuzana Chlebová; Hana Ďúranová; Lucia Gabríny; Miroslava Kačániová; Fábio Gonçalves Macêdo deMedeiros; Roberta Targino Hoskin; Marvin L. Moncada (Food Bioengineering)
ABSTRACT The goal of this study was to establish an efficient protocol for producing bioactive‐rich mushroom extracts for food ingredients development. For this, fresh mushrooms were dried, ground, and submitted to different extraction protocols—ethanolic (EE), fermentation‐assisted (FAE), or enzyme‐assisted extraction (EAE). In addition, ultraviolet B (UV‐B) irradiation, coupled with the extraction protocols, was experimentally studied for potential improvement of extracts bioactivity and yields. The extraction yield (EY), bioactivity (total phenolic content TPC, phenolic acids, flavonoids, and antioxidant activity), α‐, β‐, and total glucan contents, and mineral content were evaluated. EAE yielded the highest EY (26.48%–31.30%) while EE resulted in the highest TPC, phenolic acids, flavonoids, and antioxidant activity (p < 0.05). The β‐glucan content (0.13%–0.93%) was not affected by extraction type or UV‐B irradiation (p > 0.05). All extracts were rich in essential minerals with low potential toxicity. Based on the high EY, phenolic load, antioxidant activity, glucans, and mineral contents, EAE proved to be an effective method to obtain bioactive‐rich mushroom extracts. Overall, UV‐B irradiation did not show significant results in improving bioactivity of mushroom extracts. Our results deliver a realistic roadmap to explore mushrooms as rich sources of phytochemicals for food and nutraceuticals applications.